2016
DOI: 10.1002/tox.22307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amoxicillin exposure on brain, gill, liver, and kidney of common carp (Cyprinus carpio): The role of amoxicilloic acid

Abstract: Amoxicillin (AMX) is one of the most commonly prescribed antibiotics around the world due to its broad-spectrum activity against different bacterial strains as well as its use as a growth promoter in animal husbandry. Although residues of this antibacterial agent have been found in water bodies in diverse countries, there is not enough information on its potential toxicity to aquatic organisms such as the common carp Cyprinus carpio. This study aimed to evaluate AMX-induced oxidative stress in brain, gill, liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Previous studies in our research group demonstrate that the AMX generate oxidative stress, genotoxicity, and cytotoxicity in Cyprinus carpio (Elizalde-Velázquez et al, 2017;Orozco-Hernández et al, 2019). Our hypothesis that the AMX is capable to induce alterations to embryonic development and teratogenicity in D. rerio is supported by oxidative stress involved in the etiology of defective embryo development (Guérin et al, 2001).…”
Section: Introductionmentioning
confidence: 51%
“…Previous studies in our research group demonstrate that the AMX generate oxidative stress, genotoxicity, and cytotoxicity in Cyprinus carpio (Elizalde-Velázquez et al, 2017;Orozco-Hernández et al, 2019). Our hypothesis that the AMX is capable to induce alterations to embryonic development and teratogenicity in D. rerio is supported by oxidative stress involved in the etiology of defective embryo development (Guérin et al, 2001).…”
Section: Introductionmentioning
confidence: 51%
“…Catabolism of protein and osmotic imbalance under stress condition could alter the protein in the blood, and the transfer of body fluids in the intracellular compartment may increase the protein content (Pakhira et al., 2015). Elizalde-Velázquez et al. (2017) reported that the amoxicillin induced oxidative stress in brain, gill, liver and kidney of C. carpio during acute exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate a significant elevation in the activity of SOD and CAT enzymes in all the organs and tissues analysed, for the SOD activity the organ with the highest activity was the muscle followed by the liver, gill and brain in a decreasing order; the blood was the only tissue with negligible SOD activity; in the other hand, for the CAT activity the organ with the highest activity was the gill, followed by the liver, blood, muscle and brain in a decreasing order. An increase in the activity of CAT and SOD enzymes has been reported in the face of different environmental pollutants (Elizalde-Velázquez et al, 2016;SanJuan-Reyes et al, 2015;Islas-Flores et al, 2014Islas-Flores et al, 2013aSanJuan-Reyes et al, 2013;Garcia-Medina et al, 2010), since SOD and CAT enzymes represents the major reactive oxygen species (ROS) scavenging mechanisms and thereby the first line of defence against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%